Strengthening flood risk management policy and practice in the people republic of China lessons learned from the 2016 Yangtze River floods. (Metro Manila, Philippines Asian Development Bank, 2017)
Key lessons on managing flood risks from the Yangtze River floods in 2016 illustrate a connection between flood risk management, environmental management, and ecosystem sustainability.
Keywords: Climatic change -- China; Natural disasters -- Economic aspects -- China; Electronic books